The Correlation of DSD Teeth Outline Ratios to Q-Sort Smile Assessment and Smile Mesh Analysis - Hussein A. Alnajar1 , Ameer A. Altabatabaie 2 , Ahmed A. Alquzweeni3 , Tholfqar majed4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Smile beauty is considered the main goal in many cosmetic or orthodontic dental treatments. Howevermany objective and sujectives methods were developed to evaluate smile attractivesness depending on manyvariables. The purpose of this study was to develop a new method based on digital smile design teethoutlines ratios for smile esthetic evaluation and to correlate this method with Q-sort assessment methodand smile mesh variables. Frontal posed smile photograph of 48 individuals were subjected to smile meshmeasurments, digital smile design (DSD) and Q-sort assessment method. The areas of DSD teeth outlineswere measured using image J software in addition to the teeth areas lie in the outlines to calculate the ratioof each individual tooth area to its outline area and the total teeth areas to totsl outlinrs area.The results showed a significant correlation between the new method and Q-sort asseseement method,additionally there was a significant difference in individual and total teeth outlines ratios between thepleasant and unpleasant smile groups.Conclusions It was found that Digital smile design teeth outline ratios method could be considered as avaluable tool for evaluation of smile esthetics.